Pengaruh Program Kewirausahaan Sosial Terhadap Kepercayaan Merek. Studi Kasus Komunitas Disabilitas Bandung, Indonesia - Bob Foster (STMIK Mardira Indonesia, Bandung, 2018)
Difabel Punya Karya (DPK) is a social program formed by several people who concern about the equal employment rights for people with disabilities, especially in Bandung, Indonesia. The primary objective of DPK is to empower people with disabilities by providing entrepreneurial expertise starting from producing goods for the marketing process. Furthermore, DPK produces superior products marketed through social media and exhibitions in Bandung. The problem that arises in this social program is the level of consumers’ trust in the DPK’s brand itself. Brands Trust is a challenge for the success of the DPK program. This study tries to discover the effect of social entrepreneurship on brand trust in DPK program based on the social entrepreneurship theory by Shane & Venkataraman (2000) and Ballester (2004)’s brand trust theory. This study uses Partial Least Square (PLS) for data analysis, explanatory methods, and simple random sampling. Keywords : Social Entrepreneurship,Brand, Brand Trust, Community.